The implementation of spiritual and financial accountability in Islamic boarding school - Ratna Wati; Lilis Ardini; Fidiana Fidiana (Universitas Negeri Surabaya, 2022)
Islam views that accountability should not only be aimed at humans but also Allah. Pesantren, one of the Islamic-based religious institutions, has aided in addressing the educational demands of a wider segment of society. There are ongoing requests for pesantren to display accountability in more suitable ways as they obtain money from stakeholders. Since Islam believes that accountability should not only be financially oriented but is aimed at worshipping Allah and obtaining blessings, the current research aimed to introduce critical themes of pesantren accountability. We were interviewed ten key informants of Assalafi Al Fithrah Islamic Boarding School, Surabaya. By using phenomenology as a method, we found three themes of accountability. First, spiritual accountability is reflected by has a sincere heart and a noble goal. They work for more reasons than just financial aim and welfare, but to do their khidmah (dedicate or submission).They hope to assist both the students and the neighborhood surrounding the Islamic boarding school by offering welcoming places of prayer and by holding frequent Islamic preaching events. In term of program accountability, every activity or program at an Islamic boarding school must be reported in order to ensure that it is accountable. Each program is also widely published using the official Islamic boarding school web site and social media. Financial accountability is reflected by the adaptation of PSAK 45 in the preparation of financial statements. The Islamic boarding school, on the other hand, concluded that financial reporting should not be restricted to paper reporting exclusively. Real responsibility for Islamic boarding schools comes from publicly disclosing their development, at a greater sermon attended by the wider community.